Employee Discipline to Increase Productivity at U.D. Rahayu Kediri Salt Company - Astutik, Wahyuni Sri; Prasetya, Yanto Budi; Relitasari, Relitasari; Limantara, Arthur Daniel (LPPM of NAROTAMA UNIVERSITY, 2023)
This study aims to determine the application of work discipline in U.D. Salt Company. Rahayu Kediri to increase employee work productivity. The type of research used in this study is qualitative descriptive research. Interviews, observation, and documentation carry out the method of data collection. The data used are primary data and second data. The second data used includes employee attendance data, working hours, working days, sales targets, and sales realization in 2021. The results showed that the work discipline of employees at U.D. Salt Company. Rahayu Kediri, with the application of work discipline through working hours and the number of working days to increase employee work productivity, has not been maximized. The number of working hours the company has set for 8 hours per day has not been fulfilled. This was proven in December 2021 that the number of working hours should be 6,336 hours per month with 33 employees, which can only be realized at 4,032 hours per day. Also, in other months, The application of work discipline through the number of days of permission from employees as many as 33, with the number of days that should be achieved by the company as much as 792 days per month is only realized on average. The average per month is 448 days, so there is a deviation of 344 days or 43% per month. It is necessary to increase supervision and communication between superiors and subordinates, coaching, and self-development of employees through training.